The Differential Effects of Propylthiouracil and Methimazole as Graves’ Disease Treatment on Vascular Atherosclerosis Markers: A Randomized Clinical Trial - Wisnu, Wismandari; Alwi, Idrus; Nafrialdi, Nafrialdi; Harimurti, Kuntjoro; Pemayun, Tjokorda Gede D.; Jusman, Sri Widia A.; Santoso, Dewi Irawati S.; Harahap, Alida R.; Suwarto, Suhendro; Subekti, Imam (Frontiers in Endocrinology, 2021)
Background: Hyperthyroidism is related to vascular atherosclerosis. Propylthiouracil (PTU) and methimazole, might have different mechanism in preventing atherogenesis in Graves’ disease. Objective: This study aims to investigate the effect of anti-thyroid drugs on marker of vascular atherosclerosis in Graves’ hyperthyroidism. Methods: This study was a single-blind, randomized clinical trial done to 36 patients with Graves’ disease in Cipto Mangunkusumo General Hospital, Jakarta, Indonesia from June 2019 until July 2020. Diagnosis of Graves’ disease was obtained from clinical manifestation, and confirmed by TSH, free T4 and TRAb measurements. Participants were randomly assigned either to PTU or methimazole treatment and followed up for 3 months. Markers of vascular atherosclerosis were represented by adhesion molecules (intercellular adhesion molecule-1 [ICAM-1], vascular cell adhesion molecule-1 [VCAM-1], and E-selectin), carotid artery stiffness (pulse wave velocity [PWV]) and thickness (carotid intima media thickness [cIMT]). Results: By the end of the study, a total of 24 participants achieved euthyroid condition (13 from PTU group and 11 from methimazole group). After 3 months follow up, in PTU group, we noticed improvement of ICAM-1 (204.1 [61.3] vs. 141.6 [58.4] ng/mL, pre- and post-treatment, respectively; p = 0.001), VCAM-1 (837 [707–977] vs. 510 [402–630] ng/mL; p < 0.001) and E-selectin (32.1 [24.1–42.7] vs. 28.2 [21.6–36.8] ng/mL; p = 0.045) in PTU group. In methimazole group, only VCAM-1 improvement (725 [565–904] vs. 472 [367–590]; p = 0.001) was observed. Meanwhile in both groups, we found no significant changes in PWV and cIMT. Conclusion: Anti-thyroid treatment in Graves’ disease leads to improvement in adhesion molecules, with lesser effect on methimazole, whereas no significant changes in PWV and cIMT. PTU might have a better mechanism compared to methimazole in improving adhesion molecules.